2014
DOI: 10.1021/es405647e
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Molecular Mechanism for the Recalcitrance of Biochars: Interactive Effects of Carbon and Silicon Components

Abstract: Few studies have investigated the effects of structural heterogeneity (particularly the interactions of silicon and carbon) on the mechanisms for the recalcitrance of biochar. In this study, the molecular mechanisms for the recalcitrance of biochars derived from rice straw at 300, 500, and 700 °C (named RS300, RS500, and RS700, respectively) were elucidated. Short-term (24 h) and long-term (240 h) oxidation kinetics experiments were conducted under different concentrations of H2O2 to distinguish the stable car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(91 citation statements)
references
References 53 publications
(138 reference statements)
3
73
0
Order By: Relevance
“…High surface area biochars are known to adsorb efficiently heavy metals (Beesley & Marmiroli, 2011;Houben et al, 2013;Reddy & Lee, 2014;Yang et al, 2016;Zhang et al, 2013), Al Qian et al, 2016), and other inorganic ions (Beesley & Marmiroli, 2011;Chan & Xu, 2009;Dai et al, 2016;Raveendran, Ganesh, & Khilar, 1995;Wang, Xiao, et al, 2018), because of their large internal porosity (Chia et al, 2015). Last, but not least, it is worth noting that a mutual protection occurs between C and PhSi in biochar (Guo & Chen, 2014;Xiao et al, 2014), suggesting the potential of biochar for C sequestration. This protection is, however, dependent on pyrolytic temperature as it is enhanced at low pyrolytic temperatures (Xiao et al, 2014;Figures 4 and 5).…”
Section: Dsi Release From Biochar Phytolithsmentioning
confidence: 99%
“…High surface area biochars are known to adsorb efficiently heavy metals (Beesley & Marmiroli, 2011;Houben et al, 2013;Reddy & Lee, 2014;Yang et al, 2016;Zhang et al, 2013), Al Qian et al, 2016), and other inorganic ions (Beesley & Marmiroli, 2011;Chan & Xu, 2009;Dai et al, 2016;Raveendran, Ganesh, & Khilar, 1995;Wang, Xiao, et al, 2018), because of their large internal porosity (Chia et al, 2015). Last, but not least, it is worth noting that a mutual protection occurs between C and PhSi in biochar (Guo & Chen, 2014;Xiao et al, 2014), suggesting the potential of biochar for C sequestration. This protection is, however, dependent on pyrolytic temperature as it is enhanced at low pyrolytic temperatures (Xiao et al, 2014;Figures 4 and 5).…”
Section: Dsi Release From Biochar Phytolithsmentioning
confidence: 99%
“…On the other hand, Fang et al (2014) claimed that persistent free radicals (PFRs) were contained on biochar surface and could produce carboxylic groups when H 2 O 2 was added. However, carbon loss was also very obvious with the increase of H 2 O 2 concentrations (Guo and Chen, 2014), which could mainly be due to aromatic carbons decomposed by H 2 O 2 (Heard and Senftle, 1984). Kumar (2011) reported that the decomposition of aromatic carbons by H 2 O 2 was comprised of two different products: (i) aliphatic carboxylic acids; (ii) CO 2 and H 2 O.…”
mentioning
confidence: 99%
“…The biochar was considered mesoporous structure [10]. The adsorption average pore diameter was estimated as 1.58 nm by BET technique [19,40]. These results can be [41].…”
Section: Characterization Of Biocharmentioning
confidence: 99%